Wealth of children from single-parent families: Low levels and high inequality in Germany - Philipp M. Lersch; Markus M. Grabka; Kilian Rüß; Carsten Schröder (Journal of European Social Policy, 2021)
Families' economic wealth is a resource that can provide children with crucial advantages early in their lives. Prior research identified substantial variation of wealth levels between different family types with children from single-parent families being most disadvantaged. The causes of this disadvantage, how much the disadvantage varies between children and how the non-resident parents' wealth may potentially reduce the disadvantage remain unclear. To address these research gaps, we use data from the German Socio-Economic Panel (2002–17) to examine the level of and inequality in wealth for children from single-parent families using recentred influence function regression and decomposition analysis. We replicate earlier findings of a large wealth disadvantage for children in single-parent families. We find that the wealth disadvantage can be mainly explained with compositional differences in household income and employment characteristics. Beyond level differences, inequality between children from single-parent families is higher than for other family types and this inequality can only partly be explained by observed demographic and socio-economic characteristics. When considering the wealth of non-resident parents, the wealth disadvantage of children in single-parent families is reduced but remains substantial.
Keywords: D31; D1; J1; 330; Wealth; Family; Children; Inequality; Separation